Maturation of phagosomes containing different erythrophagocytic particles in primary macrophages - Inês B. Santarino; Otília V. Vieira (FEBS Open Bio, 2017)
Erythrophagocytosis is a physiological process that aims to remove damaged red blood cells from the circulation in order to avoid hemolysis and uncontrolled liberation of iron. Many efforts have been made to understand heme trafficking inside macrophages, but little is known about the maturation of phagosomes containing different types of erythrophagocytic particles with different signals at their surfaces. Therefore, we performed a comparative study on the maturation of phagosomes containing three different models of red blood cells (RBC): aged/senescent, complement‐opsonized, and IgG‐opsonized. We also used two types of professional phagocytes: bone marrow‐derived and peritoneal macrophages. By comparing markers from different stages of phagosomal maturation, we found that phagosomes carrying aged RBC reach lysosomes with a delay compared to those containing IgG‐ or complement‐opsonized RBC, in both types of macrophages. These findings contribute to understanding the importance of the different signals at the RBC surface in phagolysosome biogenesis, as well as in the dynamics of RBC removal.